Vaccination inhibits the human adenoviral transduction in a mouse keratoconjunctivitis model. Issue 26 (11th June 2021) - Fukuda, Michiko; Nakamura, Jutaro; Ito, Saori; Kawazoe, Kenji; Miyanaga, Yoshitaka; Teshigawara, Takeshi; Okuda, Kenji; Mizuki, Nobuhisa; Shimada, Masaru
Abstract: Adenovirus infections are a major cause of epidemic keratoconjunctivitis (EKC), which can lead to corneal subepithelial infiltrates and multifocal corneal opacity. In the current study, we investigated the use of an E1/E3-deleted adenovirus serotype 5 (Ad5) vector as a vaccine administered intramuscularly (IM) or intranasally (IN) against subsequent challenges with a luciferase-expressing Ad5 (Ad5-Luci) vector via eyedrop. We evaluated the adaptive immune response to Ad5 vector vaccination and confirmed a robust polyfunctional CD8 T cell response in splenic cells. Neutralizing Ad5 antibodies were also measured in the sera of vaccinated mice as well as Ad5 antibody in the eye wash solutions. Upon challenge with Ad5-Luci vector 8 weeks post the primary immunization, transduction was significantly reduced by > 70% in the vaccinated mice, which was slightly better in IM- vs . that in IN-vaccinated animals. Resistance to subsequent challenge was observed 10 months post primary IM vaccination, with sustained reduction up to 60% in the Ad5-Luci vector transduction. Passive immunization of naive mice with antisera from IM to vaccinated mice subsequently challenged with the Ad5-Luci vector resulted in approximately 40% loss in transduction efficiency. Furthermore, the mice that received IM immunization with or without CD8 T cell depletion showed > 40% and 70% reductions, respectively, in Ad8 genomic copies after Ad8 topical challenge. We conclude that Ad-vector vaccination successfully induced an adaptive immune response that prevented subsequent Ad transduction in the cornea and conjunctiva-associated tissues in a mouse model of adenovirus keratoconjunctivitis, and that both cellular and humoral immunity play an important role in preventing Ad transduction.